2023
DOI: 10.3390/plants12142743
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Genetic Loci for Rice Seedling Mesocotyl Elongation in Both Natural and Artificial Segregating Populations

Abstract: Mesocotyl elongation of rice seedlings is a key trait for deep sowing tolerance and well seedling establishment in dry direct sowing rice (DDSR) production. Subsets of the Rice Diversity Panel 1 (RDP1, 294 accessions) and Hanyou 73 (HY73) recombinant inbred line (RIL) population (312 lines) were screened for mesocotyl length (ML) via dark germination. Six RDP1 accessions (Phudugey, Kasalath, CA902B21, Surjamkuhi, Djimoron, and Goria) had an ML longer than 10 cm, with the other 19 accessions being over 4 cm. A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 50 publications
0
1
0
Order By: Relevance
“…Mesocotyl elongation and seedling emergence are determinant factors conditioning the number of individuals present in the field. Since the advent of genome sequencing technologies, several techniques have been used to identify QTLs for mesocotyl elongation in rice, including QTL-sequencing (QTL-seq), GWAS ( Lu et al, 2016 ; Wang et al, 2021 ) or linkage or association mapping ( Edzesi et al, 2023 ; Feng et al, 2023 ), and employing diverse mapping populations/germplasm and various DNA marker systems ( Huang et al, 2022 ; Edzesi et al, 2023 ). Previous studies reported QTLs associated with mesocotyl elongation ( qMEL ) on almost all chromosomes of rice 1–5, 7, 9, 11, 12 ( Lee et al, 2012 ; Lu et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Mesocotyl elongation and seedling emergence are determinant factors conditioning the number of individuals present in the field. Since the advent of genome sequencing technologies, several techniques have been used to identify QTLs for mesocotyl elongation in rice, including QTL-sequencing (QTL-seq), GWAS ( Lu et al, 2016 ; Wang et al, 2021 ) or linkage or association mapping ( Edzesi et al, 2023 ; Feng et al, 2023 ), and employing diverse mapping populations/germplasm and various DNA marker systems ( Huang et al, 2022 ; Edzesi et al, 2023 ). Previous studies reported QTLs associated with mesocotyl elongation ( qMEL ) on almost all chromosomes of rice 1–5, 7, 9, 11, 12 ( Lee et al, 2012 ; Lu et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%